Leucoagaricus thallensis (Agaricaceae; Basidiomycota), a new species from Punjab, Pakistan - Zaman Khan; Aiman Izhar; Abdul Nasir Khalid (Phytotaxa, 2023)
A new agaric species, Leucoagaricus thallensis, a member of La. sect. Leucoagaricus is described and illustrated from Pakistan. This species is mainly recognized by the combination of the orange-red fibrillose pileus with a white background, the fibrils on the stipe, and the volva. Data on macromorphology, micromorphology, DNA sequences (nrITS and nrLSU), habitat and comparison with closely related taxa are provided for each. Morphological and molecular phylogenetic differences separate our species from all other known species of Leucoagaricus proving its novelty. This study is the first contemporary taxonomic work on Leucoagaricus species from Noorpur Thal, district Khushab.